Du côté d'Orouët - Rozier, Jacques; Mounier, Colin; Cartier, Caroline; Croisy, Danièle; Guégan, Françoise (Potemkine Films, 2008)
Jacques Rozier is one of the unfortunately forgotten filmmakers of the French New Wave. He finished his debut film, the excellent "Adieu Philippine", only with difficulty and some monetary help from his friend Jean-Luc Godard, and afterwards he wouldn't make another feature for over 10 years. His second feature, "Du côté d'Orouët", is, like his debut, a charming and moving depiction of young people on vacation. Ambling and nearly plotless, the film meanders through two and a half hours of beachside antics as three friends - Caroline (Caroline Cartier), Joëlle (Danièle Croisy) and Kareen (Françoise Guégan) - take their September vacation in a seaside cabin owned by Caroline's family. It's a relaxed and simple film, and also a really beautiful one, progressing slowly and organically from carefree goofing around to the rich and subtle emotional complexity that begins to develop later in the film. Rozier is paying tribute to the joys of youth, the pleasures of a month-long escape from the day-to-day mundane slog of work and normal life, but as in "Adieu Philippine" there's a subtle undercurrent of melancholy that, as the film goes along, is increasingly laid bare beneath the surface giggling and good times. [seul-le-cinema.blogspot.de]
Keywords: DVD-Video